2010
DOI: 10.1007/s11483-010-9181-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, Mechanical and Microstructures Properties of Cellulose Derivatives Films: A Comparative Study

Abstract: The proposal in this study was to evaluate the physical properties of different biopolymers films. The materials used were: pectin, carboxyl methylcellulose, methylcellulose, hydroxyl propylcellulose, hydroxypropylmethylcellulose, and corn waxy starch; from these polysaccharides aqueous dispersions were prepared to 3% (w/v) for obtained films. In these biopolymer films, the thermal diffusivities (α) was evaluated by the Open Photoacoustic Cell method; also, their mechanical properties as tensile strength, elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
7
0
4
Order By: Relevance
“…Cellulose ester derivatives, such as cellulose acetate, cellulose triacetate and cellulose sulfate, are also fiber-and film-forming materials [145]. Moreover, their molecular weights can be varied, and therefore their aqueous viscosities and gelation properties can be tuned [143,146]. These features allow their use in several pharmaceutical formulations and for various biomedical purposes.…”
Section: Cellulose and Its Derivativesmentioning
confidence: 99%
“…Cellulose ester derivatives, such as cellulose acetate, cellulose triacetate and cellulose sulfate, are also fiber-and film-forming materials [145]. Moreover, their molecular weights can be varied, and therefore their aqueous viscosities and gelation properties can be tuned [143,146]. These features allow their use in several pharmaceutical formulations and for various biomedical purposes.…”
Section: Cellulose and Its Derivativesmentioning
confidence: 99%
“…Moreover, improved physicochemical and mechanical properties of edible films by incorporating both CMC and HPMC have been reported in various studies. [26][27][28][29] Therefore, the present study was designed to investigate the role of CMC and HPMC on the physiochemical properties of the alginate/aloe vera composite films particularly as reinforcing materials for improving the mechanical properties of these films.…”
Section: Introductionmentioning
confidence: 99%
“…This substitution pattern endows MC with excellent thermal gelation and film-forming characteristics compared with cellulose [4]. Up to now, it has been demonstrated that molecular weight (M w ) and degree of substitution (DS) of MC play critical roles in its physicochemical properties, i.e., water solubility, thermal stability, thickening, and gel-and film-forming properties [5]. Commercial MC is usually produced with an average DS value ranging from 1.4 to 1.9 mol Polymers 2021, 13, 3291 2 of 13 of OCH 3 per mol of AGU unit, which can readily dissolve in water at low temperatures to form homogeneous film-forming solutions [6].…”
Section: Introductionmentioning
confidence: 99%